Enhanced anti-tumor activity of the glycoengineered type II CD20 antibody obinutuzumab (GA101) in combination with chemotherapy in xenograft models of human lymphoma. Issue 9 (September 2014) - Herting, Frank; Friess, Thomas; Bader, Sabine; Muth, Gunter; Hölzlwimmer, Gabriele; Rieder, Natascha; Umana, Pablo; Klein, Christian
Abstract Obinutuzumab (GA101) is a novel glycoengineered type II CD20 antibody in development for non-Hodgkin lymphoma. We compared the anti-tumor activity of obinutuzumab and rituximab in preclinical studies using subcutaneous Z138 and WSU-DLCL2 xenograft mouse models. Obinutuzumab and rituximab were assessed alone and in combination with bendamustine, fludarabine, chlorambucil, doxorubicin and cyclophosphamide/vincristine. Owing to strong single-agent efficacy in these models, suboptimal doses of obinutuzumab were applied to demonstrate a combination effect. Obinutuzumab plus bendamustine achieved superior tumor growth inhibition versus rituximab plus bendamustine and showed a statistically significant effect versus the respective single treatments. Combinations of obinutuzumab with fludarabine, chlorambucil or cyclophosphamide/vincristine demonstrated significantly superior activity to rituximab-based treatment. Obinutuzumab monotherapy was at least as effective as rituximab plus chemotherapy in vivo, and obinutuzumab plus chemotherapy was superior to the respective monotherapies. These data support further clinical investigation of obinutuzumab plus chemotherapy.